Contextual Information Shifts Young Children's Understanding of Gender Constancy - Varlack, Victoria A.; deMayo, Benjamin; Kahn-Samuelson, Shira; Gallagher, Natalie M.; Rhodes, Marjorie; Olson, Kristina R. (Journal of cognition and development, 2024)
Children's understanding of the stability of gender over time has long been recognized as a hallmark of early childhood cognitive development. Prior research has argued that until roughly age 6, children do not understand that a person's gender identity remains consistent if the person undergoes a change in gendered behavior or appearance. However, this prior work has generally not given children any context as to why the behavior or appearance change is occurring. The present study showed U.S. three-to-five-year-olds a character (e.g. "Johnny") undergo such a change that occurred because of external factors (e.g. "Johnny is wearing his sister's dress because all his clothes are dirty"); we asked whether children would indicate that the character's gender was the same pre- and post-change. Children (N = 124, 52% girls, 66% non-Hispanic White) as young as 3 demonstrated an understanding of gender consistency and were significantly more likely to endorse gender consistency when they were, versus were not, given context for the change (p < 0.001, Cohen's d = 0.88). Results suggest that U.S. children take context into account when conceptualizing others' genders and believe that gender is generally consistent across transformations in behavior or appearance by age 3. We discuss the implications of these findings in light of a broader literature about children's understanding of gender constancy as well as contemporary understandings of gender that sometimes accommodate the idea that a person's gender can change.